Revisiting the Endocytosis of the M2 Muscarinic Acetylcholine Receptor - Wymke Ockenga; Ritva Tikkanen (Membranes, 2015)
The agonist-induced endocytosis of the muscarinic acetylcholine receptor M2 is different from that of the other members of the muscarinic receptor family. The uptake of the M2 receptor involves the adapter proteins of the β-arrestin family and the small GTPase ADP-ribosylation factor 6. However, it has remained inconclusive if M2 endocytosis is dependent on clathrin or the large GTPase dynamin. We here show by means of knocking down the clathrin heavy chain that M2 uptake upon agonist stimulation requires clathrin. The expression of various dominant-negative dynamin-2 mutants and the use of chemical inhibitors of dynamin function revealed that dynamin expression and membrane localization as such appear to be necessary for M2 endocytosis, whereas dynamin GTPase activity is not required for this process. Based on the data from the present and from previous studies, we propose that M2 endocytosis takes place by means of an atypical clathrin-mediated pathway that may involve a specific subset of clathrin-coated pits/vesicles.